The influence of music genre on concentration during the stroop color and word test among psychology students of Al Azhar University Indonesia - Ahmad Muhlis Habibi; Muhammad Syachda Maqadir; Jesnia Maura Khalisya; Harits Baihaqi (Privietlab, 2026)
Concentration is a crucial cognitive skill that enables individuals to maintain attention, process information effectively, and perform optionally on academic or psychological tasks. One environmental factor that can influence concentration is music, particularly its genre and tempo. Different genres of music elicit varying emotional and physiological responses, which may either enhance or disrupt focus. This study aims to examine the influence of music genres specifically EDM music, Jazz music, and a no-music condition on students’ concentration levels during the Stroop Color and Word Test (SCWT) among psychology students of Al Azhar University Indonesia. The research employed a quasi-experimental design with three groups: (1) an EDM music group featuring fast beats and high energy a music group characterized by moderate tempo and relaxing rhythm, (2) a Jazz music group characterized by moderate tempo and relaxing rhythm, and (3) a control group that performed the test in silence. Participants were 30 students from grade 11, divided equally across the three conditions. Data collected from the SCWT will be analyzed using One-Way ANOVA to determine whether there are significant differences in concentration among the groups. It is hypothesized that students exposed to jazz music will demonstrate higher levels of concentration compared to those exposed to EDM music, due to the calming and structured nature of jazz that supports attentional stability. In contrast, EDM music, characterized by rapid tempo and high arousal, is expected to reduce focus due to overstimulation. The control group, tested in silence, is predicted to show moderate concentration levels between the two experimental conditions. This study is expected to provide empirical evidence on how different music genres can influence students’ cognitive performance and contribute to educational strategies that support optimal learning environments.